The positive effect of Malaysia government corporate tax reduction initiative on public listed companies’ revenue: a longitudinal study - Annuar, Hairul Azlan; Isa, Khadijah; Hamdan, Hamdino; Salihu, Ibrahim Aramide; Solarin, Sakiru Adebola (Kolej Universiti Islam Selangor (KUIS), 2017)
The policy of gradual reduction in the corporate tax rate in Malaysia, which commenced since 1988 and continued till today, has become a cause for concern, as the benefits of such reduction have not been established at least empirically. The present study thus investigates the impact of the reduction of the corporate tax rate on the corporate tax revenue. The study adopts the theory of taxation by Ibn Khaldun – depicted as laffer curve. The analysis of the time series data for period between 1996 and 2014, using the ARDL approach, shows that the corporate tax rate has a dual effect on the corporate tax revenue over the study period. It shows an inverted U-shape relationship between corporate tax rate and corporate tax revenue and further reveals that the optimal tax rate is 25.5156%. Inferentially, a positive relationship existed between the two variables prior to the optimal tax rate and a negative relationship afterward. A further test of causality also shows a long-run unidirectional causality from corporate tax rate to corporate tax revenue. Thus, the policy of the gradual reduction of the corporate tax rate is suspected to have positive impacts on the productivity of Malaysia companies in term of increase in corporate tax revenue.